Digitalisasi kebijakan publik: tinjauan literatur tentang penerapan e-government dalam pelayanan publik - Nadya Disa Almira; Ismiati Essing; Rebecca Christy Mowilos (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study aims to analyze the implementation of e-government in public services through a Systematic Literature Review (SLR) approach. The study reviewed 71 scientific articles published between 2019–2025 related to public policy digitalization and electronic government implementation. The findings indicate that e-government has a positive impact on improving the effectiveness, efficiency, transparency, accountability, and quality of public services. Digital transformation enables faster administrative processes, easier public access to services, and increased community participation in governance. However, the implementation of digital public services still faces several challenges, including limited technological infrastructure, low digital literacy, human resource readiness, and data security issues. Therefore, strengthening digital infrastructure, improving human resource capacity, and developing supportive regulations are essential to support sustainable digital transformation in public administration.